Studi Eksperimen Optimasi Sudut Pengapian Terhadap Daya Pada Motor Bakar 4 Langkah 1 Slinder Dan Rasio Kompresi 9:1 Dengan Variasi Campuran Bensin Premium Dan Bioetanol - Irwandi Trinov; Romy Romy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Currently the amount of fuel in Indonesia is increasingly depleted especially gasoline fuel, so it is feared in the future the amount of gasoline will be depleted out and exhausted. To overcome these problems, it needs an alternative fuel, one of which is bioethanol. Bioethanol can be mixed with gasoline so it can save the use of gasoline. Most of the vehicles owned by middle to lower class society are motorcycles, which use carburetors as their fuel distribution, where the efficiency is smaller than the FI technology. The first objective of this study was to determine the maximum effective braking power, Specific Fuel Consumption (SFC) and thermal braking efficiency of each variable. The second objection is to find out the optimal angle at the concentration of bioethanol and premium gasoline mixture on the machine. The research method used is experimental method with variable of ignition angle and concentration of bioethanol and gasoline mixture. With the result, the maximum effective braking power on E20 fuel, 20o angle before TMA with 4000 rpm shaft speed of is 191.792 Watt, minimum SFC on E10 fuel, 15o ignition angle before TMA with 2000 rpm shaft rotation of 4.93 x 10-7 kg / J and the maximum thermal braking efficiency on E10 fuel, the ignition angle of 15o rotation shaft of 2000 rpm is 4.8%.Keywords: fuel distribution system, bioethanol, ignition angle